High Rates of Biomarker-Confirmed Alcohol Use Among Pregnant Women Living With HIV in South Africa and Uganda. (15th December 2019) - Raggio, Greer A.; Psaros, Christina; Fatch, Robin; Goodman, Georgia; Matthews, Lynn T.; Magidson, Jessica F.; Amanyire, Gideon; Cross, Anna; Asiimwe, Stephen; Hahn, Judith A.; Haberer, Jessica E.
Abstract : Background: Alcohol use is common among people living with HIV and particularly harmful during pregnancy. However, objective data on alcohol use in pregnant women living with HIV (WLWH) are lacking. In areas with high levels of alcohol use generally, such as South Africa and Uganda, these data are needed to inform interventions. Methods: Pregnant and nonpregnant, antiretroviral therapy-naive WLWH were recruited from outpatient clinics in South Africa and Uganda. Women provided self-report data on previous three-month alcohol use and potential mental health correlates of alcohol use (depression and stigma). Blood samples were used to measure phosphatidylethanol (PEth), an objective biomarker of recent alcohol intake. We analyzed any alcohol use (ie, any self-reported use or PEth-positive [≥8 ng/mL]) and under-reporting of alcohol use (ie, no self-reported use with concurrent PEth-positive). Results: Among pregnant WLWH (n = 163, median age was 26 [interquartile range: 23–29], median gestational age was 20 weeks [interquartile range: 16–26]), 40% were using alcohol and 16% under-reported alcohol use. Neither any alcohol use nor under-reporting of alcohol use differed significantly between pregnant and nonpregnant women or by country ( P > 0.05). Greater depression (but not greater stigma) was significantly associated with any alcohol use (adjusted odds ratio = 1.41, 95% confidence interval: [1.01 to 1.99]; P = 0.045). Conclusions: Alcohol use was prevalent and under-reported among pregnant WLWH in South Africa and Uganda, similar to nonpregnant participants, and associated with depression. General health care and antenatal clinic settings present opportunities to provide integrated alcohol-based counseling and depression treatment. Abstract : Supplemental Digital Content is Available in the Text.